Degradable tourniquet with reinforcing structure and preparation method of degradable tourniquet
By introducing degradable epoxy resin and nano-titanium dioxide accelerator into the tourniquet and adding a honeycomb reinforcement layer, the problems of difficult degradation and insufficient elasticity of rubber tourniquets are solved, and the preparation of tourniquets with efficient degradation and high elasticity is achieved.
Patent Information
- Application Number
- CN202510922067.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-07-04
Smart Images

Figure CN120617595A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tourniquet preparation, and in particular relates to a degradable tourniquet with a reinforced structure and a preparation method thereof. Background Art
[0002] Made of medical polymer materials, this long, flat tourniquet is highly flexible and suitable for single-use use in medical institutions for routine treatment, such as infusion, blood draw, and transfusion, to stop bleeding. It can also be used for emergency hemostasis in cases of limb bleeding or snake or insect bites in the wild.
[0003] The common tourniquet on the market is a rubber tourniquet. As the rubber tourniquet is discarded, it becomes medical waste rubber, and rubber is difficult to degrade, which ultimately causes the problem of difficult disposal of medical waste rubber.
[0004] However, when degradable polymers are used as tourniquet materials, their elastic properties cannot meet the high elasticity requirements of the tourniquet. Therefore, how to make a degradable tourniquet and its preparation method are currently urgent problems to be solved. Summary of the Invention
[0005] In view of the above problems, the present invention provides a degradable tourniquet with a reinforced structure and a preparation method thereof.
[0006] The first object of the present invention is achieved through the following technical solutions: A degradable tourniquet with a reinforced structure, comprising: a base layer and a reinforcing rib layer; the reinforcing rib layer is arranged on the outside of the base layer; The base layer comprises the following raw materials in parts by weight: 50-80 parts of polyethylene and 20-50 parts of accelerator; The accelerator is obtained by mixing and granulating a degradable epoxy resin, an epoxy silane coupling agent and nano titanium dioxide; The reinforcing rib layer includes a plurality of reinforcing ribs arranged on the base layer.
[0007] Furthermore, the reinforcing ribs of the reinforcing rib layer are in a mesh, twill or honeycomb shape.
[0008] Furthermore, the mass ratio of the degradable epoxy resin, epoxy silane coupling agent and nano-titanium dioxide is 55-70:1.2-3:30-45, the mixing temperature is 50-70° C., and the mixing time is 10-30 min.
[0009] Furthermore, the degradable epoxy resin is prepared by a hyperbranching reaction and an epoxidation end-capping reaction of a degradable triol and 1,6-adipic acid.
[0010] Furthermore, the hyperbranching reaction conditions are: under the action of the first organic solvent and the esterification reaction catalyst, the temperature is 90-150° C., the time is 4-8 hours, and the molar ratio of the degradable triol to 1,6-adipic acid is 2-3:3.
[0011] Preferably, in order to obtain a hyperbranched reaction product with a higher degree of branching, the hyperbranched reaction comprises: After the biodegradable triol, 1,6-hexanediol and DMF are evenly mixed, concentrated sulfuric acid is added dropwise while stirring. After the addition is complete, the mixture is heated to 90-110°C and stirred continuously for 1-2 hours. The mixture is then heated to 120-150°C and stirred continuously for 2-3 hours. The reaction is stopped and the hyperbranched reaction product is obtained after post-treatment. Furthermore, the first organic solvent is one of N,N-dimethylformamide (DMF), benzene and toluene.
[0012] Furthermore, the esterification reaction catalyst is one of concentrated sulfuric acid and p-toluenesulfonic acid.
[0013] Furthermore, the epoxidation capping reaction is a reaction between a hyperbranched reaction product and epichlorohydrin; The epoxidation capping reaction comprises: The hyperbranched reaction product and epichlorohydrin are heated to reflux for 4-8 hours, and then a second organic solvent and NaOH are added, and the mixture is heated to 50-55° C., stirred at this temperature for 4-8 hours, and the reaction is stopped. The mixture is post-processed to obtain a degradable epoxy resin.
[0014] Furthermore, the second organic solvent is one of chloroform, N,N-dimethylformamide (DMF), and toluene.
[0015] Furthermore, the degradable triol is prepared from p-hydroxyaniline and formaldehyde; the molar ratio of p-hydroxyaniline to formaldehyde is 1:3-3.2; the reaction conditions of p-hydroxyaniline and formaldehyde are: in a third organic solvent, the temperature is 50-70° C., and the reaction time is 5-8 hours.
[0016] Furthermore, the third organic solvent is one of ethanol, chloroform, and N,N-dimethylformamide (DMF).
[0017] Preferably, the reaction for obtaining the degradable triol comprises: After uniformly mixing formaldehyde aqueous solution (mass fraction 37%), p-hydroxyaniline and the third organic solvent, heating to 50-70°C, stirring at this temperature for 5-8 hours, and rotary evaporating to obtain the degradable triol.
[0018] The molecular structure of the degradable triol is shown below.
[0019]
[0020] In the present invention, processing aids (lubricants, etc.) and antioxidants are added to the raw materials of the tourniquet according to the processing properties or antioxidant properties of the tourniquet; The processing aids and antioxidants are processing aids and antioxidants for resins in this technical field, and the present invention does not specifically limit them.
[0021] Furthermore, the reinforcing ribs include the following raw materials in parts by mass: 55-65 parts of polylactic acid, 25-35 parts of polycaprolactone, 5-10 parts of nano-hydroxyapatite, 8-12 parts of polyethylene glycol (Mw=4000-6000), and 3-5 parts of triethyl citrate.
[0022] Furthermore, the reinforcing ribs are made of SEBS material.
[0023] The second object of the present invention is achieved through the following technical solutions: A method for preparing a degradable tourniquet, comprising: The polyethylene and the accelerator are melt-mixed, extruded, and molded to obtain the base layer of the degradable tourniquet; The reinforcing ribs are placed on the outside of the base layer of the degradable tourniquet, and compounded by a hot pressing compounding machine to obtain a degradable tourniquet with a reinforcing rib layer.
[0024] Beneficial effects of the present invention: The degradable tourniquet of the present invention is prepared by introducing an accelerator into polyethylene. The accelerator is a degradable epoxy resin and nano-titanium dioxide which are melt-blended and extruded into granules. The introduction of the accelerator not only utilizes the photocatalytic degradation effect of the nano-titanium dioxide on the polyethylene, but also utilizes the toughening and self-curing properties of the degradable epoxy resin to form an interpenetrating network, thereby giving the final composite good degradation performance and elastic properties. In addition, a reinforcing rib structure is added to improve the tensile strength of the tourniquet.
[0025] The reinforcing rib structure is preferably honeycomb-shaped. The honeycomb structure can effectively disperse stress and avoid local tearing caused by stress concentration. It has high tensile strength under the same mass and meets the lightweight requirements. In addition, the honeycomb mesh structure has through-holes, which can increase the degradation rate of the tourniquet and meet the degradable requirements.
[0026] Significantly: First, the degradable epoxy resin in the present invention is a degradable hyperbranched epoxy resin, and the hyperbranched structure provides a large amount of loading space for nano-titanium dioxide; Second, the degradable epoxy resin in the present invention contains a degradable structure of s-triazine rings and ester groups, wherein the ester group can be rapidly degraded by heating in an organic solvent, and the s-triazine ring can be rapidly degraded in an organic solvent (such as DMF) under heating (80-100°C) and / or catalyst (acidic or alkaline) conditions.
[0027] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the structure of the degradable tourniquet provided in the embodiment of the present application. DETAILED DESCRIPTION
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0030] The present application provides a degradable tourniquet 1 with a reinforced structure. The degradable tourniquet 1 includes a base layer 12 and a reinforcing rib layer 11. The reinforcing rib layer 11 includes a plurality of reinforcing ribs arranged on the base layer.
[0031] Optionally, the reinforcing ribs are arranged crosswise.
[0032] Optionally, the reinforcing ribs of the reinforcing rib layer are mesh-shaped, twill-shaped, or honeycomb-shaped.
[0033] Optionally, an anti-skid layer 13 is provided on the inner side of the base layer 12, and the anti-skid layer 13 is used to enhance the friction during contact. The anti-skid layer 13 may be an anti-skid pattern.
[0034] Optionally, the reinforcing ribs comprise the following raw materials by weight: 55-65 parts polylactic acid, 25-35 parts polycaprolactone, 5-10 parts nanohydroxyapatite, 8-12 parts polyethylene glycol (Mw=4000-6000), and 3-5 parts triethyl citrate. The PLA / PCL two-phase system (55-65 parts rigid PLA + 25-35 parts flexible PCL) achieves a balance of rigidity and toughness. Nanohydroxyapatite (5-10 parts) creates stress-enhancing points at the honeycomb nodes, improving compressive strength. The high hydrophilicity of polyethylene glycol (8-12 parts) accelerates liquid penetration and promotes uniform hydrolytic degradation. Triethyl citrate (3-5 parts) synergistically reduces melt viscosity with polyethylene glycol, ensuring the integrity of the complex honeycomb structure during injection molding.
[0035] Optionally, the reinforcing ribs are made of bio-based TPE material. The manufacturing method and process of TPE material are existing technologies and will not be described in detail here.
[0036] Optionally, the reinforcing ribs are made of SEBS. Specifically, SEBS is a linear triblock copolymer with polystyrene as the terminal segment and an ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block. SEBS does not contain unsaturated double bonds and therefore has good stability and aging resistance.
[0037] Among them, when the reinforcing ribs of this application are honeycomb-shaped, Figure 1 As shown, the honeycomb mesh reinforcement bar includes at least two layers of honeycomb mesh structure, thereby enhancing the tensile strength.
[0038] The following embodiments are described and tested using a degradable tourniquet with two layers of honeycomb mesh structure reinforcement ribs as an example.
[0039] Example 1 Preparation of degradable epoxy resin: A1. Mix 0.3 mol of formaldehyde in an aqueous solution (37% by mass), 0.1 mol of p-hydroxyaniline, and 150 mL of ethanol, heat to reflux, and stir for 5 h. Rotary evaporate and column purify to obtain a degradable triol. A2. After uniformly mixing 0.22 mol of degradable triol, 0.3 mol of 1,6-adipic acid and 300 mL of DMF, concentrated sulfuric acid (mass fraction of 98%, added mass is 1.5% of the total mass of the degradable triol and 1,6-adipic acid) was added dropwise with stirring. After complete addition, the mixture was heated to 110° C. and stirred for 1 h. The mixture was heated to 140° C. and stirred for 2 h. The reaction was stopped, rotary evaporated, washed with water, and dried to obtain a hyperbranched reaction product. The obtained hyperbranched reaction product and epichlorohydrin (excess amount, in this embodiment, the amount added is 0.9 mol) were heated to reflux for 4 h, rotary evaporated to remove excess epichlorohydrin, and then 300 mL of DMF and excess NaOH (in this embodiment, the amount added is 1 mol) were added. The mixture was heated to 50° C. and stirred at this temperature for 4 h. The mixture was rotary evaporated, washed with water, and the organic layer was taken and dried to obtain a degradable epoxy resin.
[0040] Example 2 Preparation of degradable epoxy resin: A1. Mix 0.32 mol of formaldehyde in an aqueous solution (37% by mass), 0.1 mol of p-hydroxyaniline, and 150 mL of ethanol, heat to reflux, and stir for 5-8 hours. Rotary evaporate and column purify to obtain a degradable triol. A2. After uniformly mixing 0.3 mol of degradable triol, 0.3 mol of 1,6-hexanedioic acid and 300 mL of DMF, concentrated sulfuric acid (mass fraction of 98%, added mass is 1.5% of the total mass of the degradable triol and 1,6-hexanedioic acid) was added dropwise with stirring. After complete addition, the mixture was heated to 90° C. and stirred for 2 h. The mixture was heated to 120° C. and stirred for 3 h. The reaction was stopped, rotary evaporated, washed with water, and dried to obtain a hyperbranched reaction product. The obtained hyperbranched reaction product and epichlorohydrin (excess amount, in this embodiment, the amount added is 0.9 mol) were heated to reflux for 8 h, rotary evaporated to remove excess epichlorohydrin, and then 300 mL of DMF and excess NaOH (in this embodiment, the amount added is 1 mol) were added. The mixture was heated to 55° C. and stirred at this temperature for 8 h. The mixture was rotary evaporated, washed with water, and the organic layer was taken and dried to obtain a degradable epoxy resin.
[0041] Example 3 Preparation of accelerator: 70 g of the degradable epoxy resin prepared in Example 1, 1.2 g of an epoxy silane coupling agent and 30 g of nano-titanium dioxide were mixed at 70° C. for 15 min, and the mixture was extruded and granulated to obtain a promoter.
[0042] Example 4 Preparation of accelerator: 55 g of the degradable epoxy resin prepared in Example 2, 3 g of an epoxy silane coupling agent and 45 g of nano-titanium dioxide were mixed at 50° C. for 30 min, and extruded and granulated to obtain an accelerator.
[0043] Example 5 Preparation of degradable tourniquet base layer: 80 parts by weight of polyethylene and 20 parts by weight of the accelerator prepared in Example 4 were melt-mixed, extruded, and molded to obtain a degradable tourniquet base layer, wherein the melt-mixing temperature was 150-170°C and the extrusion temperature was 180-230°C.
[0044] Example 6 Preparation of degradable tourniquet base layer: 65 parts by weight of polyethylene and 35 parts by weight of the accelerator prepared in Example 4 were melt-mixed, extruded, and molded to obtain a degradable tourniquet base layer, wherein the melt-mixing temperature was 150-170°C and the extrusion temperature was 180-230°C.
[0045] Example 7 Preparation of degradable tourniquet base layer: 50 parts by weight of polyethylene and 50 parts by weight of the accelerator prepared in Example 4 were melt-mixed, extruded, and molded to obtain a degradable tourniquet base layer, wherein the melt-mixing temperature was 150-170°C and the extrusion temperature was 180-230°C.
[0046] Example 8 Preparation of honeycomb mesh reinforcement bars: Weigh 55 parts of polylactic acid, 25 parts of polycaprolactone, 5 parts of nanohydroxyapatite, 8 parts of polyethylene glycol (Mw = 4000), and 3 parts of triethyl citrate, add them into a high-speed mixer, and mix them at 60°C for 15 minutes.
[0047] The mixed raw materials were added into a twin-screw extruder, the extrusion temperature was controlled at 160°C, the screw speed was 100 r / min, and the extruded material strips were obtained and then pelletized.
[0048] The pellets were placed in an injection molding machine and injection molded using a honeycomb mesh mold at an injection temperature of 170°C and a pressure of 80 MPa to obtain honeycomb mesh reinforcement bars.
[0049] Example 9 Preparation of honeycomb mesh reinforcement bars: 65 parts of polylactic acid, 35 parts of polycaprolactone, 10 parts of nanohydroxyapatite, 12 parts of polyethylene glycol (Mw = 6000), and 5 parts of triethyl citrate were weighed and added to a high-speed mixer and mixed at 80°C for 30 minutes.
[0050] The mixed raw materials were added into a twin-screw extruder, the extrusion temperature was controlled at 180°C, the screw speed was 150 r / min, and the extruded material strips were obtained and then pelletized.
[0051] The pellets were placed in an injection molding machine and injection molded using a honeycomb mesh mold at an injection temperature of 190°C and a pressure of 120 MPa to obtain honeycomb mesh reinforcement bars.
[0052] Example 10 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 5 and place it on a flat and clean operating table.
[0053] The honeycomb mesh reinforcement strip prepared in Example 8 was placed on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0054] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 150°C, the pressure to 50 MPa, and the hot press time to 2 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0055] Example 11 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 6 and place it on a flat and clean operating table.
[0056] The honeycomb mesh reinforcement strip prepared in Example 8 was placed on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0057] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 160°C, the pressure to 60 MPa, and the hot press time to 3 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0058] Example 12 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 7 and place it on a flat and clean operating table.
[0059] The honeycomb mesh reinforcement strip prepared in Example 8 was placed on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0060] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 170°C, the pressure to 80 MPa, and the hot press time to 5 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0061] Example 13 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 5 and place it on a flat and clean operating table.
[0062] Take the honeycomb mesh reinforcement bar prepared in Example 9 and place it on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0063] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 155°C, the pressure to 55 MPa, and the hot press time to 2.5 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0064] Example 14 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 6 and place it on a flat and clean operating table. Take the honeycomb mesh reinforcement bar prepared in Example 9 and place it on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0065] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 165°C, the pressure to 65 MPa, and the hot press time to 3.5 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0066] Example 15 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 7 and place it on a flat and clean operating table. Take the honeycomb mesh reinforcement bar prepared in Example 9 and place it on the upper surface of the degradable tourniquet base layer to ensure accurate positioning.
[0067] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 170°C, the pressure to 80 MPa, and the hot press time to 4 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0068] Example 16 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 5 and place it on a flat and clean operating table.
[0069] Take the honeycomb mesh reinforcement strip made of SEBS material and place it on the upper surface of the degradable tourniquet base to ensure accurate positioning.
[0070] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 150°C, the pressure to 50 MPa, and the hot press time to 2 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0071] Example 17 Preparation of degradable tourniquet: Take the degradable tourniquet base layer prepared in Example 6 and place it on a flat and clean operating table.
[0072] Take the honeycomb mesh reinforcement strip made of SEBS material and place it on the upper surface of the degradable tourniquet base to ensure accurate positioning.
[0073] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 160°C, the pressure to 60 MPa, and the hot press time to 3 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0074] Example 18 Take the degradable tourniquet base layer prepared in Example 7 and place it on a flat and clean operating table.
[0075] Take the honeycomb mesh reinforcement strip made of SEBS material and place it on the upper surface of the degradable tourniquet base to ensure accurate positioning.
[0076] The degradable tourniquet base layer, with the honeycomb mesh reinforcement strips placed, was transferred to a hot press laminating machine. The hot press temperature was set to 170°C, the pressure to 80 MPa, and the hot press time to 5 minutes. The hot press laminating machine was started to embed the honeycomb mesh reinforcement strips into the degradable tourniquet base layer, resulting in a degradable tourniquet with honeycomb mesh reinforcement strips.
[0077] Comparative Example 1 Preparation of tourniquet: Compared with Example 5, the accelerator in the raw materials was deleted, and the rest were the same.
[0078] Comparative Example 2 Preparation of tourniquet: Compared with Example 5, the accelerator was replaced with the accelerator prepared in the following steps, and the rest were the same: 70 g of the degradable epoxy resin prepared in Example 1 and 1.2 g of an epoxy silane coupling agent were mixed at 130° C. for 15 min, and the mixture was extruded and granulated to obtain an accelerator.
[0079] The tourniquets obtained in Examples 5-7, 10-18 and Comparative Examples 1-2 were made into test specimens and subjected to the following physical property tests and degradation tests. The test results are shown in Table 1.
[0080] Degradation test: The tourniquets obtained in Examples 5-7, 10-18 and Comparative Examples 1-2 were cut into pellets, immersed in DMF and nitric acid (the hydrogen ion concentration of the solution was calculated as 1 M), and maintained at 85±5°C for 2 hours. The pellets were then taken out, washed with water, washed with ethanol, and dried, and then subjected to a photodegradation test (after 240 hours of ultraviolet irradiation at 290-400 nm, washed with water, washed with ethanol, dried, tested for weight, and calculated for degradation rate).
[0081] In the tensile test, 10 cm of the tourniquets obtained in Examples 5-7, 10-18 and Comparative Examples 1-2 were taken and stretched to twice their original length for half a minute, repeated three times, and then the length after rebound was measured after waiting for 3 minutes.
[0082] Table 1
[0083] From the data in Table 1, it can be seen that the granules of the tourniquets obtained in Examples 10-18 have good elasticity, rebound performance and degradability.
[0084] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A degradable tourniquet with a reinforced structure, characterized in that: include: A base layer and a reinforcing rib layer; the reinforcing rib layer is arranged on the outside of the base layer; The base layer comprises the following raw materials in parts by weight: 50-80 parts of polyethylene and 20-50 parts of accelerator; The accelerator is obtained by mixing and granulating a degradable epoxy resin, an epoxy silane coupling agent and nano titanium dioxide; The reinforcing rib layer includes a plurality of reinforcing ribs arranged on the base layer.
2. The degradable tourniquet with a reinforced structure according to claim 1, characterized in that: The reinforcing ribs of the reinforcing rib layer are in a mesh shape, a twill shape or a honeycomb shape.
3. The degradable tourniquet with a reinforced structure according to claim 1, characterized in that: The mass ratio of the degradable epoxy resin, epoxy silane coupling agent and nano-titanium dioxide is 55-70:1.2-3:30-45, the mixing temperature is 50-70° C., and the mixing time is 10-30 minutes.
4. The degradable tourniquet with a reinforced structure according to claim 1, characterized in that: The degradable epoxy resin is prepared by subjecting a degradable triol to a hyperbranching reaction and an epoxidation end-capping reaction with 1,6-adipic acid.
5. The degradable tourniquet with a reinforced structure according to claim 4, characterized in that: The hyperbranching reaction conditions are: under the action of a first organic solvent and an esterification reaction catalyst, a temperature of 90-150° C., a time of 4-8 hours, and a molar ratio of degradable triol to 1,6-adipic acid of 2-3:
3.
6. The degradable tourniquet with a reinforced structure according to claim 4, characterized in that: The epoxidation capping reaction is a reaction between a hyperbranched reaction product and epichlorohydrin; The epoxidation capping reaction comprises: The hyperbranched reaction product and epichlorohydrin are heated to reflux for 4-8 hours, and then a second organic solvent and NaOH are added, and the mixture is heated to 50-55° C., stirred at this temperature for 4-8 hours, and the reaction is stopped. The mixture is post-processed to obtain a degradable epoxy resin.
7. The degradable tourniquet with a reinforced structure according to claim 4, characterized in that: The degradable triol is made from p-hydroxyaniline and formaldehyde; The molar ratio of p-hydroxyaniline to formaldehyde is 1:3-3.2; The reaction conditions of the p-hydroxyaniline and formaldehyde are as follows: in a third organic solvent, at a temperature of 50-70° C., and for 5-8 hours.
8. The degradable tourniquet with a reinforced structure according to claim 1, characterized in that: The reinforcing ribs include the following raw materials in parts by mass: 55-65 parts of polylactic acid, 25-35 parts of polycaprolactone, 5-10 parts of nano-hydroxyapatite, 8-12 parts of polyethylene glycol (Mw=4000-6000), and 3-5 parts of triethyl citrate.
9. The degradable tourniquet with a reinforced structure according to claim 1, characterized in that: The reinforcing ribs are made of SEBS material.
10. The method for preparing a degradable tourniquet with a reinforced structure according to claim 1, characterized in that: include: The polyethylene and the accelerator are melt-mixed, extruded, and molded to obtain the base layer of the degradable tourniquet; The reinforcing ribs are placed on the outside of the base layer of the degradable tourniquet, and compounded by a hot pressing compounding machine to obtain a degradable tourniquet with a reinforcing rib layer.
Citation Information
Patent Citations
Degradable hyperbranched epoxy resin and preparation method thereof
CN108794727A
Disposable tourniquet
CN206576911U
Pressurizing tourniquet for wound after puncture in department of hematology
CN217793209U
Hemostatic dressing and method for manufacturing the same
US20230285628A1
Method of processing polyethylene and polyethylene / elastomer blends
US6124428A